Mesiodistal and buccolingual crown diameters of permanent teeth - Ozge Uslu-Akcam; Rumeysa Yıldız (BMC Oral Health)
Abstract Background This study aimed to determine normative values for mesiodistal and buccolingual crown diameters of permanent teeth in the Turkish population and compare them with values reported in previous studies for other populations and the Turkish population. Materials and methods The mesiodistal and buccolingual diameters of permanent teeth were measured using digital calipers from dental cast models of 200 patients. The data analysis was conducted employing the SPSS 21 package software. The descriptive statistics were obtained for all parameters. Student t-test was utilized to compare the measurements between male and female patients. A paired t-test was used to compare the right and left side teeth. The significance level was set at 0.05. Results A total of 4800 teeth were measured. Men’s tooth sizes were larger than women’s tooth sizes. A stronger sexual dimorphism was observed in the buccolingual diameter in comparison to the mesiodistal diameter. No clinically significant differences were observed between antimeric teeth. In the maxilla and mandible, the first molars were found to have the largest mesiodistal and buccolingual diameters, whereas mandibular central teeth had the smallest diameters. Conclusions Current norm values of mesiodistal and buccolingual diameters of permanent teeth in the Turkish population were established. The norm values presented are close to the tooth dimensions in studies carried out on other populations. Compared to previous studies, there is an increase in mesiodistal diameters in the Turkish population, with this increase being more pronounced in males. The mean mesiodistal and buccolingual diameters of permanent teeth can be useful for orthodontists, prosthodontists, anatomists, anthropologists, and forensic dentistry specialists.